Biopesticides : pest management and regulation - Bailey, Alastair (CABI, 2010)
Biological controls that utilize natural predation, parasitism or other natural mechanisms, is an environmentally friendly alternative to chemical pesticides. This book addresses the challenges of insufficient information and imperfectly understood regulatory processes in using biopesticides